좌표계산을 통해 동영상의 안면 특징점 분석을 중심으로 한 웹 기반 발표 태도 교정 프로그램 개발 - 권기현(Kihyeon Kwon); 안수호(Suho An); 박찬정(Chan Jung Park) (한국콘텐츠학회 논문지, 22(2), 2022)
In order to improve formal presentation attitudes such as presentation of job interviews and presentation of project results at the company, there are few automated methods other than observation by colleagues or professors. In previous studies, it was reported that the speaker's stable speech and gaze processing affect the delivery power in the presentation. Also, there are studies that show that proper feedback on one's presentation has the effect of increasing the presenter's ability to present. In this paper, considering the positive aspects of correction, we developed a program that intelligently corrects the wrong presentation habits and attitudes of college students through facial analysis of videos and analyzed the proposed program's performance. The proposed program was developed through web-based verification of the use of redundant words and facial recognition and textualization of the presentation contents. To this end, an artificial intelligence model for classification was developed, and after extracting the video object, facial feature points were recognized based on the coordinates. Then, using 4000 facial data, the performance of the algorithm in this paper was compared and analyzed with the case of facial recognition using a Teachable Machine. Use the program to help presenters by correcting their presentation attitude. 학생들의 취업을 위한 면접 발표와 회사에서의 프로젝트 결과 발표 등과 같은 형식적인 발표 태도가 개선되려면 동료나 교수자의 관찰에 의한 방법 이외에 자동화된 방법은 드물다. 기존 연구에 따르면, 발표자의 안정적인 발화와 시선 처리가 발표에서의 전달력에 영향을 미친다고 한다. 또한, 본인 발표에 대한 적절한 피드백이 발표자의 발표 역량을 늘이는 효과가 있다는 연구도 있다. 본 연구에서는 이와 같은 교정의 긍정적 측면을 고려하여 대학생들의 잘못된 발표 습관과 태도를 동영상의 안면 분석을 통해 지능적으로 교정해 주는 프로그램을 개발하고 성능을 분석하였다. 개발하는 프로그램은 웹 기반으로 군말 사용 여부를 확인하고 안면 인식과 발표 내용 텍스트화를 통해 개발되었다. 이를 위해 군말 분류 인공지능 모델을 개발하였고, 동영상 객체 추출 후, 좌표에 기반으로 얼굴 특징점을 인식하였다. 이후 4,000개 안면 데이터를 이용해 Teachable Machine에서 안면 인식한 경우와 본 연구의 알고리즘 성능을 비교·분석하였다. 프로그램을 이용해 발표 태도를 자기스스로 교정하여 발표자들에게 도움을 준다.